IMPLEMENTASI PROJECT BASED LEARNING PADA MATERI MENERAPKAN INSTALASI SOFTWARE APLIKASI DI SMK NEGERI 1 BANYUANYAR: SMK NEGERI 1 BANYUANYAR - TOFAN DWI TJAHYONO (Mitra Pendidikan, 2021)
The development of information technology in this century is increasingly widespread, not only in the field of software but also in the field of hardware, so students must learn to recognize various types of applications that can be installed on hardware. Therefore, it is necessary to have a formulation that brings students to a higher level of creativity. with sufficient time, in accordance with the time used for one concept of discussion, in order to achieve the curriculum that has been set at school also the use of media and models that are not too difficult can make it easier for students and teachers in carrying out learning. The learning model in question is a project based learning model. This study concludes that the implementation of Project Based Learning has a positive impact on Class X TKJ ACP students on the subject of implementing application software installations at SMK Negeri 1 Banyuanyar. Students can learn to build projects that they can use after graduation